Differentially Methylated Epiloci Generated from Numerous Genotypes of Contrasting Tolerances Are Associated with Osmotic-Tolerance in Rice Seedlings - Xia, Hui; Huang, Weixia; Xiong, Jie; Yan, Shuaigang; Tao, Tao; Li, Jiajia; Wu, Jinhong; Luo, Lijun (Frontiers in Plant Science, 2017)
DNA methylation plays an essential role in plant responses to environmental stress. Since drought develops into a rising problem in rice cultivation, investigations on genome-wide DNA methylation in responses to drought stress and in-depth explorations of its association with drought-tolerance are required. For this study, sixty-eight rice accessions were used for an evaluation of their osmotic-tolerance related to 20% PEG6000 simulated physiological traits. The tolerant group revealed significantly higher levels of total antioxidant capacity and higher contents of H2O2 in both normal and osmotic-stressed treatments, as well as higher survival ratios. We furthermore investigated the DNA methylation status in normal, osmotic-stressed, and re-watering treatments via the methylation-sensitive amplification polymorphism (MSAP). The averaged similarity between two rice accessions from tolerant and susceptible groups was approximately 50%, similar with that between two accessions within the tolerant/susceptible group. However, the proportion of overall tolerance-associated epiloci was only 5.2% of total epiloci. The drought-tolerant accessions revealed lower DNA methylation levels in the stressed condition and more de-methylation events when they encountered osmotic stress, compared to the susceptible group. During the recovery process, the drought-tolerant accessions possessed more re-methylation events. Fourteen differentially methylated epiloci (DME) were respectively generated in normal, osmotic-stressed, and re-watering treatments. Approximately, 35.7% DME were determined as tolerance-associated epiloci. Additionally, rice accessions with lower methylation degrees on DME in the stressed conditions had a higher survival ratio compared to these with higher methylation degrees. This result is consistent with the lower DNA methylation levels of tolerant accessions observed in the stressed treatment. Methylation degrees on a differentially methylated epilocus may further influence gene regulation in the rice seedling in response to the osmotic stress. All these results indicate that DME generated from a number of genotypes could have higher probabilityies for association with stress-tolerance, rather than DME generated from two genotypes of contrasting tolerance. The DME found in this study are suspected to be good epigenetic markers for the application in drought-tolerant rice breeding. They could also be a valuable tool to study the epigenetic differentiation in the drought-tolerance between upland and lowland rice ecotypes.